The Relationship Between Language Learning Strategy And Reading Comprehension Students Of Sman 1 Unaaha - . Sukmawati (Cetta: Jurnal Ilmu Pendidikan, 2018)
The following objectives of this study are (1) to investigate whether between language learning strategy and reading comprehension has a significance correlation or not; (2) to examine how far learning strategy affects students reading comprehension (3) to examine what learning strategy and reading comprehension are mostly employed by the students of SMA 1 Unaaha, (4) to examine of the sixth aspect of language learning strategy which aspect correlate more strongly to reading comprehension. The result in the first hypotesis shows that there is a significance correlation language learning strategy to reading comprehension. The second hypothesis the contribution of language learning strategy to reading comprehension is only 14.8% and 85.2% is explained by the other factor that is not include in the model. The result of the third hypothesis indicates that most of English Department students in SMAN 1 Unaaha Employed metacognitive strategy, cognitive and memory strategy very often in learning English as a foreign language than the other strategy; affective, social and compensation strategy. The last hypothesis shows that the stronger correlation between the six aspects of learning strategy to the levels of reading comprehension lie on the correlation between metacognitive to literal comprehension, metacognitive to interpretive comprehension and the last is the correlation between cognitive to literal comprehension.